2022
DOI: 10.5194/tc-16-2745-2022
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ground ice melting to the expansion of Selin Co (lake) on the Tibetan Plateau

Abstract: Abstract. Selin Co, located within permafrost regions surrounded by glaciers, has exhibited the greatest increase in water storage among all the lakes on the Tibetan Plateau over the last 50 years. Most of the increased lake water volume has been attributed to increased precipitation and the accelerated melting of glacier ice, but these processes are still not sufficient to close the water budget with the expansion of Selin Co. Ground ice meltwater released by thawing permafrost due to continuous climate warmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…We assume that the long-term subsidence is equivalent to the thickness of excess ground ice released from the original ground material. The released ground ice meltwater can be calculated via the following conversion of Equation 3 (Wang et al, 2022b).…”
Section: Translation From Terrain Deformation To Ground Ice Meltwater...mentioning
confidence: 99%
See 2 more Smart Citations
“…We assume that the long-term subsidence is equivalent to the thickness of excess ground ice released from the original ground material. The released ground ice meltwater can be calculated via the following conversion of Equation 3 (Wang et al, 2022b).…”
Section: Translation From Terrain Deformation To Ground Ice Meltwater...mentioning
confidence: 99%
“…SBAS‐InSAR utilizes multi‐master‐image InSAR pairs of small temporal‐spatial baselines to reduce the effects of decorrelation and is suitable for permafrost environments that undergo severe temporal decorrelation. Several studies have applied Sentinel‐1 data SBAS‐InSAR in monitoring deformation over permafrost terrain on the Tibetan Plateau (J. Chen et al., 2022; Daout et al., 2020; Daout et al., 2017; Lu et al., 2020; Reinosch et al., 2020; Wang et al., 2022a, 2022b, 2022; X. Zhang et al., 2019). According to research, the seasonal deformation over the Tibetan plateau is normally less than 50 mm, and thaw subsidence rates are normally between 5 and 20 mm/a, with certain ice‐rich permafrost regions having subsidence rates higher than 30 mm/year (J. Chen et al., 2022; Wang et al., 2022a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the results of dynamic monitoring of lakes by many scholars have shown that climate change on the Tibetan Plateau has led to massive melting of glaciers, sufficient precipitation and surface runoff replenishment and other comprehensive factors, resulting in lake expansion and lake inundation areas [66]. Most scholars discuss the impact of the expansion of a single lake, and there are few studies on the lake inundation area of the Tibetan Plateau [14,15].…”
Section: The Importance Of Continuous Monitoring and Evaluation Of In...mentioning
confidence: 99%
“…Cheng et al [13] evaluated the impact of the rapid expansion of Lake Angzi Co on adjacent villages. Chen and Wang et al [14,15] have shown that the level of the Selin Co Lake has been rising in recent years, leading to the inundation of surrounding high-quality grasslands, and the decline of animal husbandry has had a serious impact on local herdsmen. Although Liu and Wu et al [16,17] have recognized that inundation is an important factor affecting the landscape changes around the lake, there is still a lack of systematic and quantitative research on how the inundation process of different characteristics affects the landscape changes in the inundated area.…”
Section: Introductionmentioning
confidence: 99%